Impact of Component Variability on Biomass Production and Soil Organic Carbon in Traditional Agroforestry Systems - Goswami, Sandhya; Verma, K. S.; Pala, Nazir A. (Indian Forester, 2017)
The present study was carried out on a tributary of Giri river in Kwalkhad watershed Himachal Pradesh, India. The watershed is covered by the survey of India topographical map 53F/I (1:50,000). We estimated the change in biomass production and SOC of different agroforestry systems having wide variation in component structures. Structural composition of different agroforestry systems showed wide variation in the land area covered. Agri-silvi-horticulture (0.08- 2.00 ha) and Silvipasture (0.08-5.06 ha) systems had the largest variation and possessed 23 and 16 number of units respectively. The average farm size for Agri-silvi-horticulture, Agri-horti-silviculture, Agri-silviculture, Agri-horticulture and Silvipasture was 0.69, 0.79, 0.49, 0.33 and 1.74 ha, respectively. In different tree based land use systems Silvipasture system had the widest range of accumulated biomass i.e. 6.24q to 427.38q whereas Agri-silvicultural system showed the narrow range of 11.93q- 39.42q for the same. Soil organic carbon also varied under different system's units. At the depth of 0-20&20-40 cm, trend was observed with mean values 1.54, 1.64, 1.71, 1.82 and 2.57 per cent for Agri-horti-silviculture, Agrihorticulture, Agri-silviculture, Agri-silvi-horticulture and Silvipasture respectively.